Sulle orme di Racine e Metastasio: Il castigo di Atalia di David Franco-Mendes (Altre Modernità, 2011)
Atalia's Punishment by David Franco-Mendes is a biblical drama which belongs to the period of the  Hebrew Haskalah. The author declares openly that he was inspired by the works of Racine and Metastasio,  but although it is possible to identify many common features, there are also important differences. The character of Atalia is deprived of a tragic stature which could inspire sympathy in the reader,  while all the elements of the text regarding the Temple of Jerusalem and the coronation of the legitimate  heir to the lineage of David are amplified. In this way, the drama, as compared to the works of Racine  and Metastasio, is brought back to be closer to the sensibility of a Jewish audience. Its being written  according to the canons of modern literature, and in pure Biblical Hebrew, however, makes it ideally  accessible to an educated audience of non-Jewish origin. The work can then be interpreted as an attempt  to mediate between the Jewish and non-Jewish European culture, in the spirit of the Haskalah.